Phenolic bioactives as antiplatelet aggregation factors: the pivotal ingredients in maintaining cardiovascular health - Sharifi-Rad, Javad (2021)
Cardiovascular diseases (CVD) are one of the main causes of mortality in the world. The development of these diseases has a specific factor—alteration in blood platelet activation. It has been shown that phenolic compounds have antiplatelet aggregation abilities and a positive impact in the management of CVD, exerting prominent antioxidant, anti-inflammatory, antitumor, cardioprotective, antihyperglycemic, and antimicrobial effects. Thus, this review is intended to address the antiplatelet activity of phenolic compounds with special emphasis in preventing CVD, along with the mechanisms of action through which they are able to prevent and treat CVD. In vitro and in vivo studies have shown beneficial effects of phenolic compound-rich plant extracts and isolated compounds against CVD, despite that the scientific literature available on the antiplatelet aggregation ability of phenolic compounds in vivo is scarce. Thus, despite the current advances, further studies are needed to confirm the cardioprotective potential of phenolic compounds towards their use alone or in combination with conventional drugs for effective therapeutic interventions.